Folate Deficiency Triggers the Abnormal Segregation of a Region With Large Cluster of CG-Rich Trinucleotide Repeats on Human Chromosome 2 - Garribba, Lorenza; Vogel, Ivan; Lerdrup, Mads; Gonçalves Dinis, Marisa M.; Ren, Liqun; Liu, Ying (Frontiers in Genetics, 2021)
Folate deficiency is associated with a broad range of human disorders, including anemia, fetal neural tube defects, age-associated dementia and several types of cancer. It is well established that a subgroup of rare fragile sites (RFSs) containing expanded CGG trinucleotide repeat (TNR) sequences display instability when cells are deprived of folate. However, given that folate sensitive RFSs exist in a very small percentage of the population, they are unlikely to be the cause of the widespread health problems associated with folate deficiency. We hypothesized that folate deficiency could specifically affect DNA replication at regions containing CG-rich repeat sequences. For this, we identified a region on human chromosome 2 (Chr2) comprising more than 300 CG-rich TNRs (termed ‘FOLD1’) by examining the human genome database. Via the analysis of chromosome shape and segregation in mitosis, we demonstrate that, when human cells are cultured under folate stress conditions, Chr2 is prone to display a ‘kink’ or ‘bending’ at FOLD1 in metaphase and nondisjunction in anaphase. Furthermore, long-term folate deprivation causes Chr2 aneuploidy. Our results provide new evidence on the abnormalities folate deficiency could cause in human cells. This could facilitate future studies on the deleterious health conditions associated with folate deficiency.